Error Analysis and Teaching Strategies of Chinese Time Adverbs â€œZaiâ€ and â€œCaiâ€ for Indonesian Students - Noviana, Laurencia (Bina Nusantara University, 2019)
This research aimed at investigating Indonesian studentsâ€™ mastery of Chinese adverbs zai (å†) and cai (æ‰). Modern Chinese adverbs were a difficult point in teaching Chinese as a foreign language. The time adverb of modern Chinese, zai (å†) and cai (æ‰), was an adverbial adverb easily misused by Indonesian students because these two adverbs had the same counterpart in Indonesian language. This research conducted a questionnaire survey among 83 Indonesian students in China. The questionnaire was a test about the use of time adverbs zai (å†) and cai (æ‰). The sentences that test 10 questions all came from the BCC corpus of Beijing Language and Culture University. After investigation, it is found that Indonesian studentsâ€™ errors are more obvious. The researcher hopes that it can supplement the research achievements of Indonesian students in learning Chinese adverbs, and arouse more scholars to study the characteristics of learning Chinese adverbs for Indonesian students and promote the development of Chinese language teaching in Indonesia.